Pharmaceutical applications of Aloe vera - Huay Chin Heng; Mohd Hanif Zulfakar; Pei Yuen Ng (Faculty of Pharmacy Universitas Gadjah Mada, Yogyakarta, Skip Utara, 55281, Indonesia, 2018)
Aloe vera has been used as folk medicine for a host of therapeutic indications of which the inner gel is the component extensively used and studied. Proponents of the use of this plant suggest that it is easily available, economical, and have fewer side effects compared to commercial drug compounds. However, the active constituents and their exact mechanisms have yet to be fully elucidated. This review focuses on the identification of the active constituents and their functional mechanism in the areas of anti-diabetic, anti-inflammatory, wound healing, and antibacterial. Preliminary evidence was found to support the antidiabetic effect which extended to the early stages of the disease with no adverse effects at the dosages used. Although topical application for its anti-inflammatory effect may be delayed and minute, oral administration has shown a significant response. However, too high a dose has been linked with an initial inflammatory reaction. Favorable response to the gel has also been demonstrated to support the use of A. vera in wound-healing and as an antibacterial agent, although limited to simple, uncomplicated wounds. Different active constituents such as acemannan and aloin have been suggested for the effects of the plant and this may be interpreted as synergism among different compounds rather than the action of a single compound. Until robust evidence is available, the plant should only be used as an adjunct to other well-established evidence-based treatment modalities.